Veterinarians’ perspectives on livestock diseases and antimicrobial use in Palestine - Ibrahim M. Alzuheir (Veterinary World)
Background and Aim: The livestock sector is a crucial component of Palestine’s agricultural economy, supporting food security and rural livelihoods. However, challenges such as infectious diseases, limited diagnostic resources, and antimicrobial misuse impact animal health and public safety. This study investigates veterinarians’ perspectives on disease prevalence and antimicrobial use in Palestinian livestock, providing the first comprehensive analysis of antimicrobial resistance (AMR) in veterinary practice in the region.